Origin and abundance of beach debris in the Balearic Islands - Lorena Martinez-Ribes; Gotzon Basterretxea; Miquel Palmer; Joaquín Tintoré (Scientia Marina, 2007)
The abundance, nature and possible sources of litter on 32 beaches on the Balearic Islands (Mediterranean Sea) were investigated in 2005. Mean summer abundances in the Balearics reached approximately 36 items m-1, with a corresponding weight of 32±25 g m-1, which is comparable to the results of other studies in the Mediterranean. Multivariate analyses (principal component analysis and redundancy analysis) confirmed strong similarities between islands and a statistically significant seasonal evolution of litter composition and abundance. In summer (the high tourist season), debris contamination expressed as item abundance was double that in the low season and showed a heterogeneous nature associated with beach use. Cigarette butts were the most abundant item, accounting for up to 46% of the objects observed in the high tourist season. In contrast, plastics related to personal hygiene/medical items were predominant in wintertime (67%) and natural wood was the most important debris by weight (75%). In both seasons, litter characteristics suggested a strong relationship with local land-based origins. While beach users were the main source of summer debris, low tourist season litter was primarily attributed to drainage and outfall systems.